The History of Curriculum in Current Historical-Educational Research - Freixo Mariño, María Xosé (2002)
Curriculum is a broad concept that is not limited only to the content level but also includes the methodologies to be used, the sequence of actions related to the teaching-learning process, and their evaluation. It includes an educational philosophy as a supportive element, some values, objectives, teaching strategies, spaces, resources, and many other aspects of the curriculum, about which there is little research.